PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) KOMUNAL CLUSTER RIVERPLACE PERUMAHAN TIRTASANI KABUPATEN MALANG - Dr. Dra. Utami Retno Pudjowati, M.Si; Muhamad Zenurianto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
Tirtasani Estate doesn’t have communal wastewater treatment which makes the water polluted. To solve those problems, the writer intended to design wastewater treatment plant. This thesis aimed to (1) find the waswater discharge (2) design the wastewater treatment plant (WWTP) system (3) estimate the cost of WWTP manufacturing.The data needed for this design were the map of the housing, Tirtasani estate’s topographic map, Work Unit Price of Malang District 2018. The data were obtained from site surveys.The design resulted in (1) 85.6 m3 / day wastwater discharge (2) wastewater discharge made into f 4” wastewater pipe; 3 unit of 30 m3 WWTP tank with Anaerobic aerobic system ; 3.25 m x 9.5 m x 3.5 m WWTP structure. Keywords: communal, design, WWTP